A randomized, investigator-blinded, controlled, split-scalp study of the efficacy and safety of a 1550-nm fractional erbium-glass laser, used in combination with topical 5% minoxidil versus 5% minoxidil alone, for the treatment of androgenetic alopecia - Poonkiat Suchonwanit (2020)
© 2019, Springer-Verlag London Ltd., part of Springer Nature. Fractional 1550-nm erbium-glass (Er:Glass) laser therapy is effective in inducing hair regrowth. Combining fractional Er:Glass laser therapy with topical minoxidil may yield therapeutic benefits for patients with androgenetic alopecia (AGA). To compare the efficacy and safety of fractional Er:Glass laser used in combination with topical 5% minoxidil versus 5% minoxidil alone for the treatment of male AGA, 30 men with AGA were randomized to 24 weeks of split-scalp treatment using fractional Er:Glass laser and 5% minoxidil on one side (combined therapy) or 5% minoxidil alone on the other side (monotherapy). The primary outcome was the difference in hair density and diameter, from baseline, between two treatment sides, at week 24. The secondary outcome was a global photographic assessment, evaluated by two dermatologists and the participants. Adverse events were evaluated. Twenty-nine participants completed the 24-week study period. Combination therapy provided significantly superior results for both the primary and secondary outcomes (all p < 0.05). No serious adverse events were identified for either treatment. In conclusion, combination therapy, consisting of fractional Er:Glass laser and topical minoxidil, is a promising treatment option for AGA. Laser-induced photothermolysis and the formation of effective routes for transdermal drug delivery are possible mechanisms. clinicaltrials.in.th, identifier TCTR20160912001.